Systematic Literature Review Filsafat Idealisme dalam Pembentukan Karakter Siswa - Emilya, Septi (Yayasan Sembilan Pemuda Indonesia, 2024)
The philosophy of Idealism in the formation of student character in school is a foundation in instilling moral, ethical, spiritual values that can be used as the main foundation in life in the world. In the current independent curriculum education, the concept of idealism education is needed especially in the approach and teaching in the classroom in order to achieve the educational goal of making students think critically, universally and have a character in accordance with the profile of Pancasila students. This study aims to determine the relationship between the philosophy of idealism in the formation of student character. This study uses the SRL method (systematic literature review). Data collection is obtained from the results of data collection from similar previous studies. The 15 journals obtained and used in this study are national journals from the Google scholar data base. The results obtained in this study are that there is a very close relationship between the philosophy of idealism in the formation of student character, especially in instilling religious, moral and ethical values. Another thing found in this study is the renewal of the idealism education curriculum which is included in the current independent curriculum learning.